Two hundred volumes of Agricultural Systems: Common themes and trends. (August 2022) - Snow, Val; Stephens, Emma; Martin, Guillaume; van Wijk, Mark; Timsina, Jagadish; Reidsma, Pytrik; Klerkx, Laurens; Topp, Cairistiona; Taffi, Marianna
Abstract: This editorial observes 200 volumes of Agricultural Systems . Volume 1, dated January 1976, began with an article by the inaugural editor, C.R.W. Spedding (1976), that laid the foundations for this journal. We echo that first editorial with this contribution to begin Volume 201 and review some aspects of the history of the journal. To celebrate those 200 volumes, we have prepared a Collection of the highly-cited papers published over the last 46 years in those volumes. Here we present brief summary information about the journal, compare themes common to the opening editorial and the highly-cited papers, and conclude with an intent to review the aims and scope of the journal over the next year or so.